Mesatua Bali Sebagai Pengenalan Kosa Kata Bahasa Bali Sehari-hari Pada Anak Usia Dini di Pratama Widya Pasraman Gurukula - Septiari Dewi, Putu Ayu; Susanthi Pradnya Paramitha, Ni Made Ayu; Tri Wahyuni, Ni Nyoman (Generasi Emas, 2023)
Providing an introduction to vocabulary in early childhood is very effectively done by providing storytelling activities. Mesatua Bali is a tradition of telling stories from the Balinese people that is carried out by parents to their children before the child goes to sleep. This almost lost tradition was adopted by several PAUD institutions as storytelling activities at school. The problems to be solved in this research are; Finding the method used by the teacher in Balinese mesatua activities and analyzing the vocabulary used in Balinese satua. The purpose of this study was to explore teacher methods in Balinese mesatua activities. Research using qualitative methods with a descriptive approach. Sources of data are teachers and students of Primary Widya Pasraman Gurukula. Data collection is done by observation and interviews. Data analysis uses the theory of humanism, bi-haviorism and 4 levels of Balinese language concepts. (alus, mider, andap, kasar). The results of this study indicate that the method used by the teacher is the demonstration method and the question and answer method. Based on a qualitative analysis of Balinese mesatua activities, it shows 23 new vocabulary words that can be memorized by children from the three units brought by the teacher.